Controlling gelation with sequence: Towards programmable peptide hydrogels. (1st October 2016) - Medini, Karima; Mansel, Bradley W.; Williams, Martin A.K.; Brimble, Margaret A.; Williams, David E.; Gerrard, Juliet A.
Graphical abstract: Abstract: The self-assembling peptide IKHLSVN, inspired by inspection of a protein-protein interface, has previously been reported as one of a new class of bio-inspired peptides. Here the peptide, dubbed littleSven, and modifications designed to probe the resilience of the sequence to self-assembly, is characterised. Although the parent peptide did not form a hydrogel, small modifications to the sequence (one side chain or an N -terminus modification) led to hydrogels with properties (eg. gelation time and rheology) that could be tuned by these small alterations. The results suggest that peptides derived from protein-protein interfaces are resilient to changes in sequence and can be harnessed to form hydrogels with controlled properties. Statement of Significance: Natural occurring self-assembly peptides are attractive building blocks for engineered bionanomaterials due to their biocompatibility and biodegradability. The bio-inspired self-assembly peptide, IKHLSVN, was used as a template to design peptides that readily formed hydrogels. The peptide sequence was specifically tuned to create a bionanomaterial with different properties that could be exploited downstream for a broad range of applications: nanowires, drug release, vaccine adjuvant, tissue engineering. We describe how small modifications to the parent peptide alter the amyloid-like characteristics and gel strength for each peptide.